O funcionamento das relações de discurso na dimensão dramatúrgica de entrevistas jornalísticas: uma abordagem interacionista - Daniel Martins de Brito (2023)
This research aims to study the role played by discourse relations, proposed by the School of Geneva (or the Geneva Approach to Discourse Analysis), and their correspondent text relation markers, such as connectors, in the dramaturgical dimension of written journalistic interviews. The relations are: argument, counter-argument, comment, reformulation, preliminary, topicalization, succession and clarification. The dramaturgical dimension corresponds to the process of how the interactants manage in their discourse faces and territories relations between them. We adopted an interactionist approach in order to study to what extent the interlocutors (interviewer and interviewee) negotiate faces and territories through discourse relations. This approach, based on theoretical-methodological contributions from the School of Geneva, highlights the importance of the role played by these relations in the process of facework. Adopting the interactionist approach, our study is guided by the hypothesis that the discourse relations the speaker establishes allow them to anticipate possible objections from the other (interlocutor or third party) regarding the offensive nature of their intervention, in an attempt to make this other not evaluate such intervention as an attack on their face and/or an invasion of their territory. Thus, according to this hypothesis, using these relations constitutes a language maneuver essentially linked to the dramaturgical dimension of discourse. In order to achieve our goal, we analyzed a corpus composed of eight written interviews published by Folha de S. Paulo in February 2021. From a methodological point of view, the analysis was carried out in five steps. In the first, the interviews were segmented into acts, which, according to the School of Geneva, are the minimal textual constituent of analysis. In the second, we identifed the interactive discourse relations established between the textual constituents of the interviews. In the third step, we identifed the objections the speaker tried to avoid using interactive relations. In the fourth, we investigated the damage these objections could cause to the faces and the territories at stake. In the last step, we verified the effectiveness of the relations established by the speaker in blocking a possible objection by the interlocutor. With this analysis, it was possible to verify that the discourse relations are resources that interviewee and interviewer can use to effectively anticipate each other's possible objections, and, therefore, block these objections. Because these are potentially threatening to the faces at stake, the establishment of relationships constitutes a language action directly linked to the dramaturgical dimension of the interaction, insofar as it helps the interlocutors to protect their faces and their territories from the harm caused by such objections by blocking them.